Impairment of memory generalization in preclinical autosomal dominant Alzheimer’s disease mutation carriers - Petok, Jessica R. (Neurobiol Aging, 2018)
Fast, inexpensive and noninvasive identification of Alzheimer’s disease (AD) before clinical symptoms emerge would augment our ability to intervene early in the disease. Individuals with fully-penetrant genetic mutations causing autosomal dominant Alzheimer’s disease (ADAD) are essentially certain to develop the disease, providing a unique opportunity to examine biomarkers during the preclinical stage. Using a generalization task that has previously shown to be sensitive to medial temporal lobe pathology, we compared preclinical individuals carrying ADAD mutations to non-carrying kin to determine whether generalization (the ability to transfer previous learning to novel but familiar recombinations) is vulnerable early, before overt cognitive decline. As predicted, results revealed that preclinical ADAD mutation carriers made significantly more errors during generalization than non-carrying kin, despite no differences between groups during learning or retention. This impairment correlated with left hippocampal volume, particularly in mutation carriers. Such identification of generalization deficits in early ADAD may provide an easily implementable and potentially linguistically and culturally neutral way to identify and track cognition in ADAD.